Timing of Nitrogen Fertilisation and the Effect of Poultry Manure on the Performance of Grapevines on Sandy Soil. IL Leaf Analysis, Juice Analysis and Wine Quality - Conradie, W.J. (South African Journal of Enology and Viticulture, 2017)
The effects of timing of nitrogen fertilisation and of different sources (organic vs inorganic) on leaf analysis, juice analysis and wine quality for grapevines on a sandy soil with low organic material were investigated over a period of nine years. Two Vitis vinifera L. cultivars, viz. Bukettraube (white) and Heroldrebe (red), both grafted onto Ramsey, were used. The control (No) received no N, while three treatments each received SO kg N/ha in inorganic form. The N was applied either as three equal installments, split between budbreak, fruitset and post-harvest (N1), or as a single application at budbreak (Ni), or as a single post-harvest application (N3). A fifth treatment (N4) received SO kg N/ha at budbreak in the form of poultry manure. Total Nin leaf blades and petioles, sampled at fruitset, tended to be highest for Ni and lowest for N0, but differences were relatively small. The N03-N in petioles showed larger differences, with the value for No generally being significantly lower than that of inorganically fertilised treatments. A single application of N at budbreak (Ni), delayed maturity for both cultivars, while this was also the case for split applications (N1) for the more vigorous cultivar (Bukettraube). Total Nin juice was lowest for No and N4 and higher for N1, Ni and N3, for both cultivars. In the case of Bukettraube, assimilable N was lowest for No, while the other treatments did not differ. For Heroldrebe, with a lower sugar content, assimilable N was lowest for No, Nz and N4 and higher for N1 and N3. Arginine was the predominant amino acid, constituting 61 % and 40% of total amino-N for Bukettraube and Heroldrebe, respectively. Wine quality (Bukettraube only) was always lowest for No and higher for Ni, Ni and N3. During most seasons quality did not differ between the latter three treatments. However, with Nz being more prone to fungal diseases, wine quality was reduced for this treatment when climatic conditions favoured Botrytis cinerea infection. Wine from the organic treatment (N4) scored marginally higher than N1, Nz and N3. Under the conditions of this trial, split applications of N (budbreak, fruitset, post-harvest) or a single application during the post-harvest period, or application of organic N ensured highest wine quality. Reaction to N may be different for less vigorous rootstocks.